Related factors to HIV/AIDS prevention behavior of adolescents in Jakarta’s high school - Ratnawati, Diah; Setiawan, Agus; Widyatuti, Widyatuti; Hastono, Sutanto Priyo; Siregar, Tatiana; Anggraini, Nourmayansa Vidya (International Journal of Public Health Science (IJPHS), 2024)
Adolescents are developing self-maturity, so they should have the correct views to become a person with a positive self-concept. Therefore, this period requires the role of parents. The parental roles include educating, teaching, disciplining, and protecting children to reach adulthood according to social norms. However, adolescents prefer to spend time with their peers, so peers are dominant in influential and modeling aspects of adolescents' sexual behavior with their partners. One of the behaviors compulsorily concerned is human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) prevention behavior. This study aimed to determine the relationship between characteristics, communication quality, parenting, peer roles, and HIV/AIDS prevention behavior in adolescents at “Y” Senior High School in North Jakarta. This study employed a cross-sectional research design. Samples were taken using the purposive sampling technique, and 208 students were obtained from 432 students. Gender, parental communication quality, and peer roles affected HIV/AIDS prevention behavior. The dominant variable was parental communication quality (OR=0.509). After controlling for gender and peer role characteristics, adolescents with strong parental communication quality were 0.51 times more likely to participate in HIV/AIDS-positive preventive activities than those with poor parental communication quality. Adolescents are expected to communicate with their parents, especially about sexual issues, more openly.